Long-term survival after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) for patients with peritoneal metastases of urachal cancer. Issue 9 (September 2019) - Mertens, Laura S.; Behrendt, Mark A.; Mehta, Akash M.; Stokkel, Laura; de Jong, Jeroen; Boot, Henk; Horenblas, Simon; van der Heijden, Michiel S.; Moonen, Luc M.; Aalbers, Arend G.J.; Meinhardt, Wim; van Rhijn, Bas W.G.
Abstract: Introduction: Urachal adenocarcinoma (UrAC) is a rare malignancy arising from persistent urachal remnants, which can cause peritoneal metastases (PM). Currently, patients with this stage UrAC are considered beyond cure. Our objective is to report long-term oncological outcome after cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) for patients with PM of urachal adenocarcinoma (UrAC). Materials and methods: We identified 55 patients with UrAC treated at our hospital between 1994 and 2017. Patients were staged with CT, bone scintigraphy and/or PET/CT. From 2001 on, cN0M0 patients underwent staging laparoscopy. Ten patients had PM and were treated with CRS/HIPEC; 35 showed no metastases and underwent local treatment; 10 had distant metastases and received palliative chemotherapy. Disease-specific survival (DSS) rates were estimated using the Kaplan-Meier method and log-rank tests. Postoperative complications represent a secondary outcome. Results: The median follow-up was 96.8 months. Of the CRS/HIPEC patients, 5 (50%) developed a recurrence; 4 (40%) died of disease. The 2-yr and 5-yr DSS after CRS/HIPEC were 66.7% and 55.6%, respectively. DSS of the CRS/HIPEC patients did not significantly differ from DSS of patients without metastases who only underwent curative local treatment and was superior to patients with distant metastases (P = 0.012). The overall complication rate after CRS/HIPEC was 60%. Major complications (Clavien 3) constituted 20%. The study is limited by its retrospective nature and the small sample size. Conclusion: CRS/HIPEC demonstrates satisfactory long-term oncological outcome for patients with PM of UrAC. It may be offered as a potentially curative treatment option for this group of patients.